Látható fénnyel aktiválható lizinszármazékok szintézise epigenetikai kutatásokhoz - Telek András (2019)
Activation and deactivation of gene expression in nature is regulated with high spatiotemporal resolution by a very complex system. Manipulation of this complex system can help us to get better understanding of gene regulation provided that it is carried out with similarly precise spatiotemporal resolution. Such precision of external control can be achieved by light to induce instantaneous changes at specific sites in order to carry out dynamic investigations. Light-controlled gene activation/deactivation can be accomplished by the use of photocaged non-canonical amino acids encoded into regulatory proteins e.g. histons.17 Amongst the many visible-light decageable protecting groups described in literature, 7-diethylamino-coumarinbased derivatives meet the best the criteria required for usage in proteins.18 To this end, we designed and synthesized a set of coumarin-caged non-canonical aminoacids (ncAAs). These lysine derived ncAAs carry a visible-light sensitive cageing group at the ε-amino group. Lys is a key element in many processes regulating gene expression, and it also plays important roles in the active site of many enzymes.19 The prepared compounds proved to be stable under physiological conditions, and are efficiently decaged by blue-light irradiation, so their applicability in biological experiments seem to be promising. In photolysis experiments we used a commercially available blue LED light source with emission maximum at around 462 nm. For the incorporation of the non-canonical amino acids we applied amber suppression technique involving aminoacyl-tRNA-synthase (PylRS) and tRNA (tRNSPyl) from Methanosarcina mazei.